The use of electric scooters during COVID-19 lockdown in Kuwait: safety considerations - Sharaf Alkheder (Urbanization, Sustainability and Society)
Purpose – Standing electric motorized scooters (e-scooters) have grown in prominence as an alternate method of mobility since their debut in 2017. Despite the numerous advantages, such kind of transportation is dangerous due to the risk of accidents and consequent injuries. Kuwait banned the usage of electric scooters on public roads in 2020. Thereby, an alternate solution was proposed in this research. This paper aims to study the implementation of electric scooters in Kuwait, their advantages & disadvantages and challenges they might face to be adopted as a sustainable mode of transportation in the society. Design/methodology/approach – To select the best solution, a survey of 20 questions was created and analyzed. Besides, logistic regression has been used to identify the factors that have an impact on the probability of an accident. Findings – As a result, age, usage of scooters, opinion about safety and presence of another party all had a significant impact on the probability of an accident. Based on the results of the survey, the solution for creating a special lane for electronic scooters has been proposed. The solution was presented for two Kuwait areas: Sheikh Jaber Bridge and Salem Sabah Al-Salem Al-Sabah Street. The new plans were provided in the research. It is expected that the implementation of this solution will solve the problem of accidents as well as provide sufficient social distancing during the pandemic and reduce traffic jams. Originality/value – This work presents a new trend in Gulf Cooperation Countries, taking Kuwait as an example, that depend mostly on car usage. Introducing environment-friendly modes of transportation such as scooters will bring many benefits to the society such as pollution reduction and enhancing physical activity in the community. This will add also to the literature in this domain as almost no similar studies can be seen in the literature for this region of the world.